2020
DOI: 10.1158/1535-7163.mct-19-1166
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of New Targets to Control Metastasis in Pancreatic Cancer by Single-cell Transcriptomics Analysis of Circulating Tumor Cells

Abstract: ◥Metastasis development is the leading cause of cancer-related mortality in pancreatic ductal adenocarcinoma (PDAC) and yet, few preclinical systems to recapitulate its full spreading process are available. Thus, modeling of tumor progression to metastasis is urgently needed. In this work, we describe the generation of highly metastatic PDAC patient-derived xenograft (PDX) mouse models and subsequent single-cell RNA-sequencing (RNA-seq) of circulating tumor cells (CTC), isolated by human HLA sorting, to identi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 37 publications
0
23
0
Order By: Relevance
“…First, we consider the case where the EMT score of the tumor is known; this is a typical scenario if gene expression from a tumor sample is analyzed, either at a single‐cell or bulk resolution. For instance, we calculate the MLR scores of several samples from a pancreatic ductal patient‐derived xenograpt model [43]; on average, the samples are predicted to be hybrid E/M (1.13± 0.14). In the model, constraining the tumor EMT score to a fixed value is equivalent to selecting a contour line on the two‐dimensional (k, c) parameter space (Figure 5B, left).…”
Section: Resultsmentioning
confidence: 99%
“…First, we consider the case where the EMT score of the tumor is known; this is a typical scenario if gene expression from a tumor sample is analyzed, either at a single‐cell or bulk resolution. For instance, we calculate the MLR scores of several samples from a pancreatic ductal patient‐derived xenograpt model [43]; on average, the samples are predicted to be hybrid E/M (1.13± 0.14). In the model, constraining the tumor EMT score to a fixed value is equivalent to selecting a contour line on the two‐dimensional (k, c) parameter space (Figure 5B, left).…”
Section: Resultsmentioning
confidence: 99%
“…These makers are found to be distinct subpopulation and are used to navigate management of cancer [ 27 ]. Dimitrov et al [ 28 ] isolated CTCs from the PC mouse models having liver and lung metastasis. They clustered the single-cell RNA sequencing as per their expressing profile including cell cycle molecules and extracellular matrix-associated genes taken from both primary and metastatic samples.…”
Section: Application Of Single-cell Technology In Detecting Pc Cellsmentioning
confidence: 99%
“…Another meaningful study using scRNA-seq identified heterogeneity between primary and metastatic lesions, confirming that BIRC5 expression was massively upregulated in metastatic CTCs. YM155 administration in a model with BIRC5 deletion shrank the metastatic foci in SW1990-bearing mice, thus indicating that BIRC5 in CTCs is a key coordinator of the metastasis of pancreatic cancer ( 71 ).…”
Section: Single-cell Sequencing In Cancer: Lessons Learnedmentioning
confidence: 99%